Analyses of COVID-19 in Japan by the Mathematical Model of SIR - Saito, Takesi (European Journal of Applied Sciences, 2022)
The COVID-19 in Japan is analyzed by means of the SIR equation. Contents are listed up below as 1 12. In Sec. 4, the basic reproduction numbers for the 5 and 6 waves in Japan are determined as 2.5 and 5, respectively. Here we make use of data of the removed number, rather than that of the infective number, because the latter seems to be ambiguous. Other important contents are discussed about the stronger the infection power, the smaller the number of deaths in Sec5, an area theorem of infection curves for large basic reproduction number in Sec.9, introducions of vaccine effect and a rate of people with self-control into the SIR model in Sec.11, and finally a logistic formula for organic extinctions in Sec.12.